WHY SHOULD WE SLEEP? - Davlatova , Kamola (Scientific practical conference, 2026)
This article explores the biological, psychological, and cognitive importance of sleep as a vital human need. Drawing from recent scientific studies, it examines how sleep contributes to body restoration, hormone regulation, emotional balance, and memory consolidation. The paper also analyzes the consequences of chronic sleep deprivation on mental health, learning abilities, and physical well-being. Additionally, it highlights the necessity of maintaining proper sleep hygiene and offers recommendations for developing healthy sleeping habits in the digital age.